2016
DOI: 10.1146/annurev-med-050214-013454
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana Legalization: Impact on Physicians and Public Health

Abstract: Marijuana is becoming legal in an increasing number of states for both medical and recreational use. Considerable controversy exists regarding the public health impact of these changes. The evidence for the legitimate medical use of marijuana or cannabinoids is limited to a few indications, notably HIV/AIDS cachexia, nausea/vomiting related to chemotherapy, neuropathic pain, and spasticity in multiple sclerosis. Although cannabinoids show therapeutic promise in other areas, robust clinical evidence is still la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
116
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(120 citation statements)
references
References 97 publications
2
116
0
2
Order By: Relevance
“…First, there has long been the concern for impairing cognition, as well as paranoia (Yarnell, 2015). Second, there is a concern for potential long-term worsening of PTSD outcomes with cannabis (Wilkinson, Yarnell, Radhakrishnan, Ball, & D'Souza, 2016). Marijuana use is positively correlated with PTSD symptoms, but, according to self-reports, cannabis was used with intent to cope with these PTSD symptoms (Bonn-Miller, Vujanovic, Feldner, Bernstein, & Zvolensky, 2007).…”
Section: Cannabinoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, there has long been the concern for impairing cognition, as well as paranoia (Yarnell, 2015). Second, there is a concern for potential long-term worsening of PTSD outcomes with cannabis (Wilkinson, Yarnell, Radhakrishnan, Ball, & D'Souza, 2016). Marijuana use is positively correlated with PTSD symptoms, but, according to self-reports, cannabis was used with intent to cope with these PTSD symptoms (Bonn-Miller, Vujanovic, Feldner, Bernstein, & Zvolensky, 2007).…”
Section: Cannabinoidsmentioning
confidence: 99%
“…Therefore, the directionality of the effects of cannabis use on PTSD symptoms cannot be fully differentiated (Yarnell, 2015). Regardless, there appears also to be a correlation between PTSD and problematic cannabis use (Wilkinson et al, 2016; Yarnell, 2015). Third, extended use may result in down-regulation of CB1 receptors (Leweke & Koethe, 2008), predisposing to a rebound anxious/depressive phenotype (Haller, Bakos, Szirmay, Ledent, & Freund, 2002; Haller, Varga, Ledent, & Freund, 2004).…”
Section: Cannabinoidsmentioning
confidence: 99%
“…The rapidly changing epidemiology of medical cannabis highlights the importance of research on the potential beneficial and adverse effects of cannabis use (Volkow et al, 2017). Although a long line of research has established associations between recreational cannabis use and adverse health outcomes (Wilkinson et al, 2016), the relationship between cannabis use and sleep appears to vary as a function of dose and timing of administration (Babson and Bonn-Miller, 2014; Conroy and Arnedt, 2014). Evidence indicated that cannabis has sedative and excitatory effects (Babson and Bonn-Miller, 2014), and cannabis withdrawal is associated with sleep disruptions (Bolla et al, 2010; Gates et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, nearly all of these were among adolescents. Given that most state MMLs list HIV/AIDS as a qualifying condition for medical use of marijuana (27), passage of MMLs may be associated with increased marijuana use among HIV+ individuals.…”
Section: Introductionmentioning
confidence: 99%